Pengaruh Kepemimpinan Transaksional Guru Melalui Media Pembelajaran Digital Terhadap Kualitas Pembelajaran Siswa - Syahreza, Hadian Firman; Gultom, Syawal; Rosnelli, Rosnelli (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research aims to analyze the influence of teachers' transactional leadership through digital literacy on the quality of student learning. In today's digital era, a teacher's ability to apply digital literacy in the learning process is crucial for creating a dynamic and participatory learning environment. Teachers' transactional leadership, characterized by active student involvement in decision-making and the freedom to express opinions, is expected to enhance the quality of student learning. The research employed a quantitative survey, with data collected through questionnaires distributed to junior high school students. The study showed that teachers who adopt a transactional leadership style and utilize digital technology in the classroom can increase student motivation, participation, and learning outcomes. Digital literacy becomes a key tool for teachers to deliver more interactive, relevant, and contemporary learning experiences. Therefore, the integration of transactional leadership and digital literacy has a significant impact on improving the quality of student learning. This research suggests enhancing digital literacy training for teachers and encouraging the application of a transactional leadership approach to support better educational quality.